Postmodernism in history : fear or freedom? - Southgate, Beverley C. (Routledge, 2003)
This book traces philosophical precursors of postmodernism and identifies some roots of current concerns. It describes the core constituents of postmodernism and provides a lucid and profound analysis of the current state of the debate. Southgate's main concern is to counter 'pomophobia' (fear of postmodernism) and to assert a positive future for historical study in a postmodern world.